Aplikasi Penginderaan Jauh dalam Pemetaan Potensi Cebakan Emas Epitermal - Abyan Gugus Pandjadi; Dono Guntoro; Novriadi (Jurnal Riset Teknik Pertambangan, 2023)
Abstract. Determining the potential for mineral deposit occurrences is a crucial step in exploration activities. This research utilizes Landsat 8 imagery in remote sensing applications to identify potential gold deposit areas. Factors such as rock lithology, geological structures, and alteration distributions are assessed. Topographic maps, geological maps, Landsat 8 imagery, and Digital Elevation Models (DEMs) from the Shuttle Radar Topography Mission (SRTM) are employed for analysis. Rock lithology identification is carried out using the Supervised Mapping method. Geological structures are identified through lineament analysis using Lineament Count Density. The distribution of altered rocks is identified using Composite RGB imagery with Bands 4/2, 6/7, and 5. Interpretation results indicate the potential for gold deposits in the Gunungapi Tapaktuan Formation, including several andesite rocks. Geological structures show lineaments with high-density intensities. The distribution of altered rocks appears in shades of yellow to orange. Data analysis yields potential gold deposit zones covering 64.7 Ha in the Northwest Block, 126.3 Ha in the Central Block, and 30.1 Ha in the South Block. While these areas suggest potential deposits, the geometry of gold deposits is yet to be confirmed. Satellite image processing results are corroborated through field observations and laboratory testing using the Atomic Absorption Spectrophotometer (AAS). Abstrak. Penentuan potensi cebakan endapan bahan galian adalah langkah krusial dalam kegiatan eksplorasi. Penelitian ini menggunakan Citra Landsat 8 dalam aplikasi penginderaan jauh untuk mengidentifikasi daerah potensi cebakan emas. Faktor-faktor seperti litologi batuan, struktur geologi, dan sebaran alterasi dievaluasi. Peta Topografi, Peta Geologi, Citra Landsat 8, dan Digital Elevation Model (DEM) dari Shuttle Radar Topography Mission (SRTM) digunakan untuk analisis. Identifikasi litologi batuan dilakukan dengan metode Supervised Mapping. Struktur geologi diidentifikasi melalui analisis kelurusan menggunakan Lineament Count Density. Sebaran batuan teralterasi diidentifikasi dengan Citra Komposit RGB Band 4/2, 6/7, dan 5. Hasil interpretasi menunjukkan potensi cebakan emas di Formasi Gunungapi Tapaktuan dengan beberapa batuan andesit. Struktur geologi menunjukkan kelurusan dengan intensitas kerapatan tinggi. Sebaran batuan teralterasi tampak dalam warna kuning hingga oranye. Analisis data menghasilkan zona potensi cebakan emas seluas 64,7 Ha di Blok Barat Laut, 126,3 Ha di Blok Tengah, dan 30,1 Ha di Blok Selatan. Meskipun luasan tersebut menunjukkan potensi cebakan, belum dapat dipastikan endapan emas secara geometri. Hasil pengolahan citra satelit dikonfirmasi melalui observasi lapangan dan pengujian laboratorium menggunakan Atomic Absorption Spectrophotometer (AAS).